Does credit default swap trading improve managerial learning from outsiders? - Kim, Jeong‐Bon; Wiedman, Christine; Zhu, Chunmei (Contemporary Accounting Research, 2023)
Abstract We investigate whether credit default swap (CDS) trading results in managers learning new information through stock prices that is relevant to their investment and forecasting decisions. We argue that the CDS market structure, the sophistication of CDS market participants, and the cleanness of CDS spreads as a signal of default risk together produce and convey information that is new to managers of firms referenced in CDS contracts. We consider two measures for managerial learning: (1) the sensitivity of managerial investments to share prices and (2) the sensitivity of changes in management forecast accuracy to stock returns. We find that both sensitivity measures increase significantly when firms are referenced in any traded CDS contracts, indicating that CDS trading improves managerial learning. We also find that the improvement in managerial learning is more pronounced for firms that are subject to higher uncertainty in industry‐specific and economy‐wide prospects, consistent with the view that CDS market participants have informational advantages with respect to the industry‐level and macroeconomic environments. We further find that the improvement in managerial learning is more evident for firms with higher credit risk. Our findings provide large‐sample evidence on a positive consequence of CDS trading in the context of managers' ability to learn from outside investors.